Role of the Bidirectional Cardiorespiratory Coupling in the Nonlinear Dynamics of the Cardiovascular System - Karavaev, Anatoly S.; Ishbulatov, Yurii M.; Bibicheva, Tatiana S.; Gridnev, Vladimir I.; Prokhorov, Mikhail D.; Ogneva, Marina V.; Kiselev, Anton R. (School on Dynamics of Complex Networks and their Application in Intellectual Robotics (Online), 2022)
healthy heart rate is irregular, and numerical measures of its complexity, such as the largest Lyapunov exponent and the correlation dimension, are perspective early markers of cardiovascular diseases. However, the origin of irregularity in the cardiovascular system is still debated, which makes it harder to give the physiological interpretation to the complexity measures. According to a prominent hypothesis, the nonlinear bi-directional cardiovascular coupling could be a source of the complexity, but experimental investigation of this theory is limited by the limitation of modern measuring equipment, nonstationarity of real biological signals, and very strict restrictions on the designs of the active experiments imposed to insure the safety of the subjects. We investigated the role of bidirectional cardiovascular coupling using a mathematical model of cardiovascular system and respiratory systems. We simulated an active experiment with the blockade of the autonomic control of respiration, which disturbed the coupling, and then measured changes in the dynamics of the cardiovascular system using spectral analysis, statistical analysis and complexity measures.